Application of rapid air sampling and non-targeted analysis using thermal desorption comprehensive two-dimensional gas chromatography/time-of-flight mass spectrometry to accidental fire. (September 2022) - Hashimoto, Shunji; Takazawa, Yoshikatsu; Ieda, Teruyo; Omagari, Ryo; Nakajima, Daisuke; Nakamura, Satoshi; Suzuki, Noriyuki
Abstract: To be able to gauge the health risks and biological effects of e-waste fires, it is of key importance to know what types and amounts of chemicals are released when they occur. In this case study, we pumped 6–24 L of air from an accidental fire at a recycling depot through a Tenax-TA tube and conducted comprehensive (non-targeted) analysis by thermal desorption/comprehensive two-dimensional gas chromatography/time-of-flight mass spectrometry (TD/GC × GC/ToFMS). A special focus was placed on the search for halogenated compounds. More than 5000 components were detected in the atmosphere around the fire; however, component separation was insufficient, even when using GC × GC. The number of organohalogen compounds retrieved was increased about 1.8-fold by the refinement process of the exact mass spectrum using mass defect filtering (MDF) software. After processed by MDF, 386 peaks were concluded to be halogenated compounds. The major retrieved substances included chlorinated (or chlorinated-brominated) dioxins, chlorinated (or brominated) phenols, benzene, and various other halogenated aromatic compounds. Direct comparison of mass spectra was carried out to investigate the potential for qualitative and quantitative comparison of detected peaks without specific identification. The approximate quantitative values are summarized for each compound in the estimated substance group. Their ratios were estimated to be halogenated phenols: 13%, benzenes: 9.6%, dibenzo- p -dioxins: 9.6%, dibenzofurans: 8.4%, biphenyls; 7.4% and toluenes: 6.4%. Graphical abstract: Image 1 Highlights: Quick sampling with portable active air sampler for use in any location. No pre-treatment and direct sample introduction for non-targeted analysis. in silico cleanup to remove mass spectra of large amounts of hydrocarbons in fire smoke. Carried out the method in real fire accident.